2012
DOI: 10.1124/jpet.111.188797
|View full text |Cite
|
Sign up to set email alerts
|

Xanomeline Modulation of the Blood Oxygenation Level-Dependent Signal in Awake Rats: Development of Pharmacological Magnetic Resonance Imaging as a Translatable Pharmacodynamic Biomarker for Central Activity and Dose Selection

Abstract: In vivo translational imaging techniques, such as positron emission tomography and single-photon emission-computed tomography, are the only ways to adequately determine that a drug engages its target. Unfortunately, there are far more experimental mechanisms being tested in the clinic than there are radioligands, impeding the use of this risk-mitigating approach in modern drug discovery and development. Pharmacological magnetic resonance imaging (phMRI) offers an approach for developing new biomarkers with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 54 publications
3
6
0
Order By: Relevance
“…An earlier study suggested that xanomeline was able to reduce the fMRI increases in BOLD response produced by the NMDA antagonist ketamine in rats (Baker et al, 2012). Here we demonstrate that xanomeline was also able to reduce the increase in high frequency EEG activity produced by ketamine while having no effect on the reduction in lower frequency α/β activity.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…An earlier study suggested that xanomeline was able to reduce the fMRI increases in BOLD response produced by the NMDA antagonist ketamine in rats (Baker et al, 2012). Here we demonstrate that xanomeline was also able to reduce the increase in high frequency EEG activity produced by ketamine while having no effect on the reduction in lower frequency α/β activity.…”
Section: Discussionsupporting
confidence: 59%
“…While previous studies have addressed neurochemical and behavioral consequences of muscarinic modulation (Mirza et al, 2003;Raedler et al, 2007;Langmead et al, 2008) the macroscopic brain circuits and functional substrates engaged by M1/M4 agonism, and xanomeline in particular, remain poorly investigated. One previous study reported that xanomeline dose-dependently reversed the ketamine-evoked pharmacological fMRI (phMRI) signal increases in the rat brain, demonstrating a modulating effect of muscarinic agonism on an aberrant glutamatergic state considered of mechanistic relevance to schizophrenia (Baker et al, 2012). Since ketamine-challenge phMRI has been successfully translated into healthy humans and modulated by both clinically approved drugs and novel glutamatergic agents (De Simoni et al, 2013a;Doyle et al, 2013;Javitt et al, 2018aJavitt et al, , 2018bMehta et al, 2018), this observation indicates a potential translational biomarker opportunity.…”
Section: Introductionmentioning
confidence: 92%
“…With use of phMRI, drug action on rodent brain function has been evaluated for a range of compounds that include amphetamine (Chen et al, 2005), nicotine (Gozzi et al, 2006), remifentanil (Liu et al, 2007), and cocaine (Schwarz et al, 2004). Previous studies have also used phMRI as a means to characterize the effects of a pharmacological pretreatment (eg, 5HT-2A receptor antagonist) on a particular challenge (e.g., phencylidine) (Gozzi et al, 2008;Gozzi et al, 2010;Chin et al, 2011;Large et al, 2011;McKie et al, 2011;Baker et al, 2012). Such studies can be highly informative with regard to understanding the underlying neurobiology (receptor and brain circuit level) that drives a certain cognitive phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…A similar inconsistency has been observed for other pharmacological compounds, such as ketamine. Here, phMRI activation in the brain is the dominant effect observed in awake, naive rodents and healthy human subjects (Chin et al, 2011;Baker et al, 2012;De Simoni et al, 2012). However, in the preclinical setting, phMRI deactivation is observed in regions, such as the cerebellum, substantia nigra, and periaqueductal gray; deactivation is minimally observed in the human subgenual cingulate cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The ketamine response can be blocked by antiglutamatergic compounds [88,89] and can reverse the phMRI signal evoked by some (but not all) antipsychotic agents and compounds designed to attenuate glutamate release [95,96]. Additional drug classes that induce phMRI signals include analgesics [97101], antipsychotics [102], cognitive enhancers [103], drugs of abuse [104,105], calcium channel blockers [106,107], cyclooxygenase-2 (COX-2) inhibitors [108], muscarinic acetylcholine receptor modulators [109111], and therapies traditionally thought to impact solely immune system activity [112]. In addition to traditional phMRI studies, pharmacological modulation of functional connectivity in animal models and humans has also been reported [113118].…”
Section: Current State Of Fmri As a Tool For Drug Developersmentioning
confidence: 99%